A methods engineering study on Moondish Foods Corporation - Molar, Ma. Theresa O. (College of Engineering, 2005)
The proponents of this study laid the foundations for work measurement at Moondish Foods Corporation, manufacturer of exotic coconut dishes such as Laing, Bicol Express, Ginataang Puso ng Saging, Ginataang Mais, and other products. By conducting methods engineering study on the processes, layout, tools and equipment used and working conditions of the company several problems were identified with the aid of problem analysis tools such as Streamline diagnostic chart and Ishikawa diagrams. Also, time studies were conducted to establish time standards and to check proper distribution of workers. Problems such as worker fatigue and unknown production capacity were identified as the main effects of problems such as inappropriate tools and utensils, improper distribution of workers, poor environmental conditions, unnecessary activities and poor material positioning. Inappropriate tools and utensils include the varying cutting tools used in the vegetable preparation area, poorly designed strainer in taro blanching and scooping utensil in the can filling section. Recommendation for these problems is the purchase of new ones that are suitable for the type of process. Moreover, purchase of appropriate containers would eliminate the unnecessary activities. Poor environmental conditions in the company such as, wet floors, exposure to excessive heat, vibration, noise and congestion of workers leads to worker fatigue that would cause reduced worker productivity. Recommendations such as revision of layout and use of proper protective gears to decrease the drastic effects of vibration and noise should be implemented to improve working conditions. If employee's working conditions is improved, it would develop better worker-management relationship. Furthermore since the company has just started practicing the principles of Total Quality Management (TQM), these would also help them achieve better production in terms of both quality and quantity of their work.